Pengembangan Aplikasi Mobile Reservasi Makeup Artist Menggunakan Metode Agile - Saputra, Ferdyn; Ikrimach, Ikrimach (Jurnal Informatika, 2024)
This research aims to develop a mobile-based makeup artist reservation system at Tanti Makeup Studio to overcome the limitations of conventional booking methods. The current manual reservation system through phone calls or walk-ins has caused several challenges, including scheduling conflicts, inaccurate booking records, lack of visibility into incoming reservations, and operational inefficiencies that hinder business growth. This research utilizes Agile methodology, which incorporates iterative development cycles and continuous feedback integration. Data collection used primary sources through interviews and direct observation, and secondary sources through literature study. The system development process includes requirements analysis, conceptual design, and is followed by implementation and black box testing. The results showed successful implementation of key features including user authentication, package management, scheduling, and payment processing, with all components achieving conformance in functionality testing. The mobile app effectively streamlines the booking process, improves operational efficiency, and enhances customer experience through an intuitive interface and integrated payment system. User validation through a survey of 51 respondents showed strong positive results: 80.4% rated the application as overall easy to use (51% “very easy” and 29.4% “easy”), 86.2% gave high ratings for ease of booking (52.9% highest rating, 33.3% second highest), 80.4% expressed satisfaction with the integrated payment system, 86.3% reported improved time efficiency in the booking process, and 82.4% felt that the confirmation and scheduling process became more efficient. This study concludes that the implemented system successfully overcame the initial challenges of the manual booking process, providing a comprehensive solution for both service providers and customers in the makeup service industry